A Review on the Recent Application of Jaya Optimization Algorithm - Alsajri, Mohammad; Mohd Arfian, Ismail; Abdul-Baqi, Saba (IEEE, 2019)
Jaya is a new metaheuristic that in recent years, has been applied to numerous intractable optimization problems. The important difference between Jaya and other optimization algorithms is that Jaya does not require the tuning of its parameters (a process needed in the other algorithms to escape unwanted convergence). Another different is the efficiency of Jaya in always choosing the best solution. In this paper, a review of the recent application of Jaya algorithm in the field of optimization problem was reviewed.